Theory of generations: features of media consumption in the conditions of active development of digital technologies - Natalya Gennadievna Maskova; Anastasia Alexandrovna Khazhgerieva (Вестник Майкопского государственного технологического университета)
The article discusses the current problems of media consumption caused by the development of digital technologies, the media market and Internet communications. Using statistical and logical research methods, the article defines the features of media consumption and identifies factors influencing the perception of information by different age audiences. The theory of generations explains the heterogeneous process of information perception among audiences of different age groups, contributes to the establishment of effective communication. It has been concluded that representatives of the media business could create more in-demand information products that meet the needs of the audience of digital media resources based on the study of the value orientations of generations.